2008
DOI: 10.1016/j.ajem.2007.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol misuse and report of recent depressive symptoms among ED patients

Abstract: Objective-This study examines the magnitude of association between alcohol misuse with recent depressive symptoms.Methods-A cross-sectional study of 412 randomly selected patients ≥18 seeking ED care.Results-51.0% reported depressive symptoms. At-risk drinking was reported by 26.0% of the sample, 28.2% scored positive for RAPS4. Alcohol abuse, and Binge drinking were reported by 25.1% and 28% of the patients, respectively. According to our results at-risk drinking (OR 2.49; CI 1.47-4.20; P ≤ .001), problem dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
(31 reference statements)
0
22
0
Order By: Relevance
“…Moreover, the possibility of the effects of long-term drinking among the respondents could enhance the likelihood for false positive results. Furthermore, when comparing this research with other cross-sectional studies, such as that of Bazargan-Hejazi et al, 10 who recruited 412 participants attending the emergency department, significant correlations between heavy alcohol consumption and depressive symptoms were found. However, those authors used emergency department patients to diagnose the incidence of depressive symptoms and did not adjust for social class or hazardous drinking in their analysis.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the possibility of the effects of long-term drinking among the respondents could enhance the likelihood for false positive results. Furthermore, when comparing this research with other cross-sectional studies, such as that of Bazargan-Hejazi et al, 10 who recruited 412 participants attending the emergency department, significant correlations between heavy alcohol consumption and depressive symptoms were found. However, those authors used emergency department patients to diagnose the incidence of depressive symptoms and did not adjust for social class or hazardous drinking in their analysis.…”
Section: Discussionmentioning
confidence: 97%
“…Causal relationship between Alcohol use disorder and depression has been attributed to AUD causing depression or depression causing AUD [19]; in the latter the person uses alcohol to relieve the depressive symptoms. In addition there may be a reciprocal causal relationship where the presence of alcohol use raises the possibility of developing the other disorder [2, 5, 14, 2025]. Individuals, who drink alcohol to reduce emotional stress, may be self-medicating themselves with alcohol [2628], and a link has been shown where depression predicted alcohol use disorder and alcohol use disorder predicted depression [29].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that ED patients with high-risk and alcohol-dependent drinking patterns are at increased risk for mental health problems relative to the general population, where the past 12-month DSM-IV prevalence of mood and anxiety disorders has been reported at 9% and 11%, respectively (Grant et al, 2006). Although comparisons with other ED studies are difficult because of methodological differences in ascertainment of mental health and alcohol problems, Bazargan-Hejazi et al (2008), in a study of alcohol misuse and recent depressive symptoms among inner-city ED patients, reported that among current drinkers, 51% had positive results on screening for recent depressive symptoms. One study of ED patients in Australia found that nearly 19% of hazardous (nondependent) drinkers reported clinically significant levels of anxiety or depression; the prevalence of mental health problems for harmful (likely dependent) drinkers was 32% in the same sample (Kinner et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Taken together, these results indicate that the ED is an appropriate setting for standardized screening for mental health problems, particularly among those presenting with alcohol-related problems. In fact, for many patients who use the ED due to lack of health insurance, the ED may be the only place individuals with mental health issues have contact with health professionals (Bazargan-Hejazi et al, 2008). Further, there is evidence that patients with alcohol use disorders and comorbid mental health disorders visit the ED at disproportionately high rates, a general phenomenon first described by J. Berkson, who found that individuals with more than one disorder are more likely to receive medical services than those with only one disorder (Berkson, 1949).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation